Clinical profile of seizure disorder in hospitalized patients in tertiary care center - A prospective cross-sectional study - Thiyagarajan, A Alagu; Selvakumar, CJ; Jenix , YA Nathan; Duraisamy, Ramesh (Asian Journal of Medical Sciences, 2021)
Background: Knowledge regarding people affected with epilepsy is essential for accurate planning and management of patients. This study was conducted to study clinical profile of seizure disorder in the patients hospitalized in a tertiary care hospital of Tamil Nadu. Aims and Objectives: To study clinical profile of seizure disorder in patients hospitalized in Coimbatore government medical college hospital. Materials and Methods: This study was a single center hospital based cross-sectional study of the clinical profile of seizure disorder in hospitalized patients at tertiary care center of Tamil Nadu, Neurology department the 2 years from 2018 to 2020. All the patients presenting with complaints of seizures were included in this study. Results: This study included a total of 321 patients with epilepsy. Their ages ranged between 10 and 100 years. 180 of the study population were males and 141 were female patients. 30% of patients had new onset seizures. Fever precipitated seizure in 16% of the subjects. Excitation, sleep deprivation, fever, watching television, and head trauma showed a strong association with generalized epilepsy. The majority of the patients had generalized tonic-clonic seizure, followed by focal neurological deficit. 98% of patients responded to treatment and they did not had recurrent episodes of seizure. Conclusion: The sample size of our cohorts is relatively small. It is possible that some prognosis factors may be missed due to the small sample size. Further studies with a larger sample cohort are required. Uneducated and low socioeconomic make people vulnerable to seizures because of lack of awareness, poor compliance to medicines, not detection of seizure provoking factor, repeated exposure to seizure provoking factor, prevalence of alcoholism, and thus lowering seizure threshold. There is a treatment gap still because of epilepsy and appropriate usage of resources will help to reduce this treatment gap and decreases epilepsy associated morbidity and mortality.